LEARNING OF RATS LIVING IN THE CONDITION OF SOCIAL ISOLATION OR OVERCROWDING TO INDIVIDUAL AND JOINT INSTRUMENTAL BEHAVIOUR - Gavrilov, V.V. (Modern Psychology, 2019)
Social stress is a widespread problem in the modern world. Stress is caused by many factors, in particular, such living conditions as isolation and overcrowding. The objective of this work was to study the speed of learning in rats with different “social” postnatal ontogenesis to perform the same instrumental food-acquisition behavior alone and cooperating with conspecific. It was shown that with insulating stress, rats need more time to learn not only cooperative but also individual instrumental behavior, while in rats kept in crowded conditions, the rate of learning both types of behavior was not significantly different from that of control group.